How rates of perinatal mental health screening in Australia have changed over time and which women are missing out - Katrina M. Moss; Nicole Reilly; Annette J. Dobson; Deborah Loxton; Leigh Tooth; Gita D. Mishra (Elsevier, 2020)
Abstract Objectives: To report rates of perinatal mental health screening from 2000 to 2017 and investigate factors associated with not being screened both antenatally and postnatally more recently (2013-2017). Methods: A longitudinal community‐based study of self‐reported perinatal mental health screening with a national sample of 7,566 mothers from the Australian Longitudinal Study on Women's Health reporting on 9,384 children. The main outcome measure was whether mothers were asked about their emotional wellbeing by a health professional, including completing a questionnaire. Results: From 2000 to 2017, the percentage of women not screened decreased from 40.6% to 1.7%. The percentage of women screened both antenatally and postnatally increased from 21.3% to 79.3%. From 2013 to 2017, women who were older (aOR, 0.65; 95%CI, 0.52-0.81) or had reported emotional distress (aOR, 0.77; 95%CI, 0.60-0.99) were less likely to have been screened both antenatally and postnatally. Conclusions: Despite improvements, perinatal mental health screening is not yet universal. One‐in‐five women are not screened both antenatally and postnatally, including women in high‐risk populations such as those who have reported emotional distress. Implications for public health: Women are in regular contact with health professionals in the perinatal period. This opportunity to detect women at risk of perinatal mental health issues is too important to be missed.